STUDI TENTANG PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI PADA KELAS XI IPS SMA NEGERI 1 KOTA MOJOKERTO - NAHDIYATUR ROSIDAH (Jurnal Pendidikan Akuntansi (JPAK), 2013)
This study purpose to determine the types of teaching materials in SMA Negeri 1 Mojokerto City and the reasons teachers choose the teaching materials, determine the feasibility of teaching materials, and study the response of students to the instructional materials used. This study is a descriptive research with quantitative approach. The results showed that the materials used in SMA Negeri 1 Mojokerto City is LKS "Focus" and the textbook "PR Ekonomi Intan Pariwara". From the review of teaching materials expert obtained the result that the teaching materials used in SMA Negeri 1 Kota Mojokerto LKS "Focus" and has categorized textbook “PR Ekonomi Intan Pariwara" very decent. The results of the students' responses to the materials they use are very good.. Keyword: teaching materials